2023
DOI: 10.3390/tropicalmed8020092
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of Hepatitis C Virus and Efficacy of Direct-Acting Antiviral Drugs among Chronic Hepatitis C Patients in a Tertiary Care Hospital

Abstract: Hepatitis C virus (HCV) chronic infection is a major causative factor for several chronic liver diseases, including liver cirrhosis, liver cell failure, and hepatocellular carcinoma. The HCV has seven major genotypes. Genotype 4 is the most prevalent genotype in the Middle East, including Saudi Arabia, followed by genotype 1. The HCV genotype affects the response to different HCV treatments and the progression of liver disease. Currently, combinations of direct-acting antiviral drugs (DAAs) approved for the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The issue is that there are still limited real-world statistics from Saudi Arabia about the effectiveness of DAAs. Therefore, there is a critical need for additional research to be done to evaluate the effectiveness of DAAs in treating people with chronic hepatitis C (Hawsawi et al, 2023). Consistent with the abovementioned idea, Huynh et al (2018) have confirmed that the whole dynamic patterns of ALT and AST during and after therapy with DAAs have not been well explored.…”
Section: Statement Of the Problemmentioning
confidence: 78%
See 1 more Smart Citation
“…The issue is that there are still limited real-world statistics from Saudi Arabia about the effectiveness of DAAs. Therefore, there is a critical need for additional research to be done to evaluate the effectiveness of DAAs in treating people with chronic hepatitis C (Hawsawi et al, 2023). Consistent with the abovementioned idea, Huynh et al (2018) have confirmed that the whole dynamic patterns of ALT and AST during and after therapy with DAAs have not been well explored.…”
Section: Statement Of the Problemmentioning
confidence: 78%
“…Identification and characterization of HCV types and subtypes have significant implications for the development of an HCV vaccine (Hawsawi et al, 2023;Zein, 2000). For the evaluation of the clinical course and the delivery of antiviral medications, genotyping of HCV has become essential (AlKahtani et al, 2019).…”
Section: Hcv Genotypes and Antiviral Treatment Effectivenessmentioning
confidence: 99%
“…The study ensured a balanced gender representation, with a predominance of females (69.23%), enriching the generalizability of the findings and facilitating gender-specific analyses. Age distribution showed a concentration in the middle-aged demographic (35-50 years), which constituted 38.4% of the participants, while younger (20-35 years) and older adults (50-65 years) were also well-represented, indicating the study's broad applicability across age groups (16)(17)(18). The methodology employed for ELISA Antibody Detection, PCR Confirmation, and Genotyping was robust, enabling a detailed examination of the participant cohort.…”
Section: Discussionmentioning
confidence: 98%